2013
DOI: 10.1007/s11250-013-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproductive performance of sambar deer in Sabal Forest Reserve of Sarawak, Malaysia

Abstract: We examined the growth, reproduction, rutting behavior, and health status of sambar deer (Cervus unicolor brookei) in secondary Acacia mangium plantation. The data were collected over 11 years from a breeding herd of 21 stags and 33 hinds in Sabal Forest Reserve, Sarawak, Malaysia. Brody's growth model of the pooled data is Y t  = 148.56 (1 - 0.98e(-0.023t)), which estimates that maximum weights of adults are 184 and 115 kg for males and females respectively. Sambar deer are nonseasonal breeders with the breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…() was used to determine the MEA in the acacia plantation according to the availability of secondary vegetation, and ECC was estimated based on BW and the physiological stages of the animals according to ECC models (Dahlan et al . ; Dahlan ; Dahlan & Dawend ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…() was used to determine the MEA in the acacia plantation according to the availability of secondary vegetation, and ECC was estimated based on BW and the physiological stages of the animals according to ECC models (Dahlan et al . ; Dahlan ; Dahlan & Dawend ).…”
Section: Methodsmentioning
confidence: 99%
“…Dahlan () indicated that deer farming in existing plantations and with marginal vegetation is feasible if a tropical deer species were used. Sambar deer are suitable as a farm species in forest plantations (Dahlan & Dawend ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They go through an annual cycle of rapid growth in preparation for the rutting season and are casted after the season (Munk, Garrison, Clemons, & Keel, 2015). They are casted and regrown from a blastema annually into three branched structures of cartilage and bone that are used for sparing and attraction in adult sambar deer (Dahlan & Dawend, 2013; Lin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the hormone levels using fecal steroid assays provide a non-invasive method and have the capacity to develop long-term means of determining adrenocortical, testicular hormones in many vertebrate taxa(Spratt, Spratt, Bauman, & Chandler, 2018). Today the animal behavioral changes are possible to relate with changes in physiological processes (Dahlan & Dawend, 2013).…”
Section: Introductionmentioning
confidence: 99%